Prolegómenos de la democracia y la primera Constitución del siglo XXI1 (1979-1980) - Gálvez Montero, José (2016)
The twelve years of  the Revolutionary Government of  the Armed Forces showed a series of transformations that should be included in the Constitution; the best known was the state intervention in the economy, which had animpact on the agricultural, industrial and educational sectors, among others. The most momentous was the proposal by legislators to put the Constitutionas the supreme rule and protective of fundamental rights that revalues humandignity at the heart of society and the state, taking into account the neoconstitutionalism perspective. Thus, the law put aside the analysis based exclusively on legal issues replacing it with an analysis that encompasses the interpretationas a principle, argument and context, which is linked with this prelude.